2017
DOI: 10.1002/adem.201700591
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Silicon Nanostructures as Anode Material for Lithium‐Ion Batteries

Abstract: Silicon (Si) is promising for high capacity anodes in lithium-ion batteries due to its high theoretical capacity, low working potential, and natural abundance. However, there are two main drawbacks that impede its further practical applications. One is the huge volume expansion generating during lithiation and delithiation progresses, which leads to severe structural pulverization and subsequently rapid capacity fading of the electrode. The other is the relatively low intrinsic electronic conductivity, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 127 publications
(154 reference statements)
0
63
0
Order By: Relevance
“…A superior gravimetric capacity of over 3000 mAh/g is a very attractive benefit of silicon compared to graphite (372 mAh/g) [50]. However, dramatic volume expansion (approximately 300%) during lithiation leads to the separation of silicon particles from the electrically conductive carbon matrix after multiple cycles, which is a significant drawback [63]. Additionally, this physical instability disrupts the solid electrolyte interphase that forms on the surface of silicon particles, promoting continued breakdown and loss of the electrolyte.…”
Section: Anodesmentioning
confidence: 99%
“…A superior gravimetric capacity of over 3000 mAh/g is a very attractive benefit of silicon compared to graphite (372 mAh/g) [50]. However, dramatic volume expansion (approximately 300%) during lithiation leads to the separation of silicon particles from the electrically conductive carbon matrix after multiple cycles, which is a significant drawback [63]. Additionally, this physical instability disrupts the solid electrolyte interphase that forms on the surface of silicon particles, promoting continued breakdown and loss of the electrolyte.…”
Section: Anodesmentioning
confidence: 99%
“…The motivation for this study comes from a combination of preliminary data observed by Jiang et al and from lithium‐ion battery research . While silicon is an attractive anode material for lithium‐ion batteries due to its high charge capacity, it also suffers from cracking and pulverization during cycling .…”
Section: Relevant Values In the Calculation Of Energy Dissipated By Tmentioning
confidence: 99%
“…[4,5] Several strategies have been proposed to address these problems. From am ateriald esign viewpoint, the principal approaches are to reduce the silicon particle size to the nano-scale, [6,7] create ap orous structure, [8][9][10] and combine silicon with conducting materials (typically carbon materials such as graphene, [11][12][13][14] carbon nanotubes, [15] amorphous carbon, [16,17] and various carbon compounds). [18,19] Furthermore, regarding electrode fabrication, the binder is an important component of Si-based electrodes.…”
Section: Introductionmentioning
confidence: 99%